« (Néo)-locuteurs » ? Repenser la catégorie à l’aune de situations migratoires - Valeria Villa-Perez (La Bretagne Linguistique)
In this paper, we examine the sociolinguistic category of neo-speaker on the basis of a case study and an extensive review of the scientific literature on the subject. More precisely, we have problematised it by relating it to speakers of a regional (and often minority) language in migratory situation, a profile that is little discussed in the literature.